Analisis Laba Industri Manufaktur Sektor Makanan yang Terdaftar di Bursa Efek Indonesia (BEI) Sebelum dan Sesudah Penyesuaian Tarif PPN Menjadi 12% - Gandana, Ega; Kurniawati , Yuyun (Program Studi Ekonomi Pembangunan Universitas Flores, 2026)
This study attempts to quantitatively measure the implications of the VAT rate adjustment from 11% to 12% on operational profitability, particularly gross profit, in the food and beverage manufacturing segment listed on the Indonesia Stock Exchange (IDX). To examine this impact, we adopted a comparative descriptive research design, comparing financial statement data from the third quarter of 2024 (pre-increase period) with the third quarter of 2025 (post-increase period). A total of 26 companies were selected through purposive sampling to be the subjects of analysis to provide an in-depth picture of this sector's adaptation to changes in tax regulations. The results of the study show that there are variations in the impact among the sample companies. Most companies experienced a decline in gross profit due to increases in raw material, distribution, and operational costs that could not be fully passed on to consumers in order to maintain sales volume (high demand elasticity). Conversely, several companies actually recorded an increase in gross profit due to managerial capabilities in cost efficiency, brand strength, and greater economies of scale in mitigating fiscal pressures. Overall, this study concludes that the resilience of companies' profits amid the 12% VAT policy shock is highly dependent on the characteristics of the product and the effectiveness of each entity's cost management.